HALAL CERTIFICATION AND LABELING AS COMPETITIVE ADVANTAGE: IMPLICATIONS FOR PROFITABILITY OF CULINARY MSMES - Silmi, Mukhamad Jauhari; Ashlihah, Ashlihah (EKSYDA: Jurnal Studi Ekonomi Syariah, 2025)
The main problem in this study is the low awareness and utilization of halal labeling and certification by MSME players, especially in the spring roll skin industry in Jombang Regency, even though the potential for the halal market in Indonesia is very large. This study aims to analyze the effect of halal labeling and certification on MSME profitability. The approach used is quantitative with survey method. Primary data was collected through distributing questionnaires to 30 MSME players who have or are in the process of obtaining halal certification. The data were analyzed systematically through the stages of validity, reliability, classical assumption tests (normality, multicollinearity, heteroscedasticity), and multiple linear regression analysis with the help of SPSS software. The results showed that both labeling and halal certification have a positive and significant effect on profitability. The practical implications of these findings indicate that halal labeling can increase consumer confidence, while halal certification opens wider market access. Therefore, MSME players need to view halal certification not only as a regulatory obligation, but as a business strategy that can increase competitiveness and business sustainability.